A study to determine the correlation between number of endoscopic gastric biopsy specimen and sensitivity of clo test in helicobacter pylori infection in Hospital Universiti Sains Malaysia - Voon Khier Ti, Kenneth (2015)
BACKGROUND: Northeastern peninsular state of Kelantan has an exceptionally low prevalence of Helicobacter Pylori infection; yet receive high volume of patients referred for Oesophago-gastroenteroscopy (OGDS) for upper gastrointestinal symptoms. CLO test is the most commonly used initial diagnostic test, but sensitivity is widely variable especially in the background of low prevalence. Amount of tissue biopsy and site of gastric biopsy may be crucial in maximizing the detection rate in this region. METHOD: 150 patients with upper gastrointestinal symptoms undergoing elective OGDS in Hospital Universiti Sains Malaysia (HUSM) were included. Four gastric mucosa biopsies were taken from each patient using a standard 2.8mm biopsy forcep, at the pre-pyloric region within 3cm from pylorus, each bite adjacent to each other. One biopsy specimen was compared with two biopsy specimens on a CLO test well, and positive results were recorded when there was colour change at 1 hour, 3 hour, 6 hour and 24 hour. The fourth specimen was sent for histopathological examination with Haematoxylin & Eosin staining, followed by Warthin-Starry staining as control to diagnose Helicobacter pylori. Data entry and analysis was done using SPSS software version 20. Mc Nemar’s test was used to compare the overall sensitivity of CLO test and sensitivity at each time between both groups to determine the earliest detection. RESULTS: Overall prevalence rate of Helicobacter pylori infection was 13.3%. Demographic pattern is consistent with previous local studies, but this study recorded a higher prevalence rate of 10.7% among Malay ethnic patients. Presentation with black tarry stool has the highest prevalence rate of infection at 22.2%, whereas endoscopic diagnosis of gastric ulcer has the highest prevalence rate of infection at 32%. Overall sensitivity of both group were equal at 75% with no statistical significance. However, speed of CLO test becoming positive was slightly higher in two biopsy group at 1 hour and 3 hour, recording sensitivities of 37.5% and 68.8% respectively, compared to single biopsy group with sensitivities of 25.0% and 37.5% respectively, without any statistical significance. CONCLUSION: This study confirmed the low prevalence of Helicobacter pylori infection in this region but suggested that the method applied may improve the detection rate, particularly among ethnic Malay population with low bacterial load in their gastric mucosa. Sensitivity of CLO test is similar with either single or double biopsy specimens, but speed of CLO test becoming positive appeared to be slightly higher with double biopsy specimens, even though statistically not significant. Both presenting symptoms and endoscopic diagnosis are poor indicator of Helicobacter pylori status in this region. However, prevalence according to racial distribution is consistent with national pattern.